2000
DOI: 10.1177/01461672002611011
|View full text |Cite
|
Sign up to set email alerts
|

When Beliefs Yield to Evidence: Reducing Biased Evaluation by Affirming the Self

Abstract: People often cling to beliefs even in the face of disconfirming evidence and interpret ambiguous information in a manner that bolsters strongly held attitudes. The authors tested a motivational account suggesting that these defensive reactions would be ameliorated by an affirmation of an alternative source of self-worth. Consistent with this interpretation, participants were more persuaded by evidence impugning their views toward capital punishment when they were self-affirmed than when they were not (Studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
476
3
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 468 publications
(502 citation statements)
references
References 46 publications
21
476
3
2
Order By: Relevance
“…On the other hand, this was not the case when solutions emphasizing personal choice (e.g., personal responsibility, donation, paying more for clean electricity) were presented; and in this case the climate frame elicited a stronger response for all subjects regardless of political orientation. This result is consistent with previous research on identity affirmation, in which individuals tend to react dismissively towards information that opposes their cultural values (Cohen et al 2000;Cohen et al 2007;Kahan 2010). In particular, a recent paper (Kahan et al 2012) found that hierarchical individualists (correlated with conservatism) were less likely to find a climate change study scientifically valid if the proposed solution involved air pollution regulation, while communitarian egalitarians (correlated with liberalism) were less likely to find it valid if the proposed solution involved geo-engineering.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, this was not the case when solutions emphasizing personal choice (e.g., personal responsibility, donation, paying more for clean electricity) were presented; and in this case the climate frame elicited a stronger response for all subjects regardless of political orientation. This result is consistent with previous research on identity affirmation, in which individuals tend to react dismissively towards information that opposes their cultural values (Cohen et al 2000;Cohen et al 2007;Kahan 2010). In particular, a recent paper (Kahan et al 2012) found that hierarchical individualists (correlated with conservatism) were less likely to find a climate change study scientifically valid if the proposed solution involved air pollution regulation, while communitarian egalitarians (correlated with liberalism) were less likely to find it valid if the proposed solution involved geo-engineering.…”
Section: Discussionsupporting
confidence: 89%
“…The self-affirmation task was based on that used by Cohen, Aronson, and Steele (2000). For the main analysis, the religiosity scale was averaged as in the previous two studies.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Even subtle differences in framing can mean the difference between acceptance and rejection of a message (28). Messages that are supported by scientific evidence are especially effective when acceptance of the message also means that one's personal values can be upheld (29,30). Messages concerning global warming and climate change are no exception: They need to be tailored with great care (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%